Evaluation of the short term effect of nursery treatments with phosphite-based products, acibenzolar-S-methyl, pelleted Brassica carinata and biocontrol agents, against lettuce and cultivated rocket fusarium wilt under artificial inoculation and greenhouse conditions. (July 2016) - Gilardi, Giovanna; Demarchi, Stefano; Gullino, Maria Lodovica; Garibaldi, Angelo
Abstract: Experimental trials have been carried out in order to evaluate the efficacy of preventative treatments based on plant defense activator products, biocontrol agents, a microbial complex with arbuscular mycorrhizal fungi, and Brassica carinata pellets against Fusarium oxysporum f. sp. lactucae race 1 on lettuce and Fusarium oxysporum f. sp. raphani on cultivated rocket under greenhouse conditions. These products were compared with fungicides known for their ability to induce host resistance (phosethyl-Al and acibenzolar-S-methyl), and with azoxystrobin. Three and four applications of the tested products were carried out on lettuce and rocket seedlings grown in nursery conditions. Treated and untreated plants were transplanted into soil infested with Fusarium wilt agents to obtain an average disease severity (DS) of 65.6–69.2 and of 56.9–62.1 on the untreated lettuce and rocket plants, respectively. The best Fusarium wilt biocontrol was obtained after four applications of Bacillus subtilis Qst713 and with the Glomas microbial complex (42 and 46.7%, efficacy, respectively). B . carinata pellets provided a consistent control when applied 14 days before the rocket and lettuce were transplanted into the infested soil. Acibenzolar-S-methyl, applied at 0.025 g/Liter, showed a DS reduction in F . oxysporum f. sp. lactucae from 36 to 61% and of F . oxysporum f. sp. raphani from 54 to 73%, thus showing statistically similar results to those of azoxystrobin, which was used as a reference (DS reduction from 59 to 65%). Although the Fusarium wilt control provided by such products was not complete in the present experimental conditions, these products can be considered interesting components for an integrated pest management of the Fusarium wilt of leafy vegetables, starting from nursey applications. Moreover, the tested BCAs could become potentially useful, especially for plant monocultures. This study has been produced new information on the effects of potassium phosphite, applied at the nursery level, on reducing lettuce and rocket fusarium wilt. An average efficacy of 69.5% was observed for lettuce, while an average efficacy of 65.2% was observed for cultivated rocket. The good fungicidal activity of the phosphite-based product, coupled with the positive effect on plant biomass, is of special interest. Highlights: The Fusarium wilt of lettuce and rocket is an emerging disease that causes severe losses. Fungicides, resistance inducers and biocontrol agents were applied at the nursery level in three/four treatments. Phosphites and acibenzolar-S-methyl were similar to azoxystrobin in the Fusarium wilt control. Four applications of Bacillus subtilis and of the microbial complex with Glomus provided the best biocontrol. The phosphite-based product provides a consistent effect on plant biomass.